Effect of Noise on the Decoherence of a Central Electron Spin Coupled to an Antiferromagnetic Spin Bath - G. C. Fouokeng; M. Tchoffo; S. Moussiliou; J. C. Ngana Kuetche; Lukong Cornelius Fai; Massou Siaka (Advances in Condensed Matter Physics)
We analyze the influence of a two-state autocorrelated noise on the decoherence and on the tunneling Landau-Zener (LZ) transitions during a two-level crossing of a central electron spin (CES) coupled to a one dimensional anisotropic-antiferomagnetic spin, driven by a time-dependent global external magnetic field. The energy splitting of the coupled spin system is found through an approach that computes the noise-averaged frequency. At low magnetic field intensity, the decoherence (or entangled state) of a coupled spin system is dominated by the noise intensity. The effects of the magnetic field pulse and the spin gap antiferromagnetic material used suggest to us that they may be used as tools for the direct observation of the tunneling splitting through the LZ transitions in the sudden limit. We found that the dynamical frequencies display basin-like behavior decay with time, with the birth of entanglement, while the LZ transition probability shows Gaussian shape.